A new approach to managing neonates born to mothers at risk for early-onset neonatal sepsis: is it cost-effective and can it reduce NICU admissions? - Nagwa Sabry; Mahmoud H. Ibrahim (Journal of Pediatric and Neonatal Individualized Medicine, 2021)
Introduction: In Minia University Hospital for Obstetrics and Gynecology and Pediatrics (Minia, Egypt), all neonates born to mothers with suspected or confirmed intrauterine inflammation or infection (triple I) or with group B Streptococcus (GBS) bacteriuria, were directly admitted to the neonatal intensive care unit (NICU) for clinical assessment and treatment of suspected sepsis for at least 48 hours, regardless of their clinical condition. Establishment of a risk-identification system for those high-risk neonates based on the EOS detection standard checklist may decrease NICU admissions and antibiotics exposure in asymptomatic neonates.